CARE Model of Treatment for stuttering: Theory, assumptions, and preliminary findings - Byrd, Courtney T.; Coalson, Geoffrey A.; Conture, Edward G. (Frontiers in Psychology, 2024)
The purpose of this article is to present a theory of therapy for stuttering, its related assumptions, and findings from associated empirical studies. Specifically, we propose the Blank Center CARE™ Model of Treatment (CT) for stuttering, which differs from the current, widely employed fluency model of treatment (FT). The CT reflects the authors’ belief in the need to move away from fluency-focused or seemingly ableist treatments (i.e., any approach that attempts to correct, cure, or fix a disabling condition) for stuttering. The authors propose a shift toward a theory of treatment that addresses whole-person wellness and considers the treatment of stuttering from outside the framework of fluency shaping and stuttering modification. In support of such considerations, this article provides preliminary findings from both non-clinical and clinical studies of using the CT for children and adults. Although preliminary, these findings appear to lend empirical support to the authors’ belief that the treatment of stuttering needs to change. In essence, a change in the zeitgeist regarding the treatment of stuttering may contribute to an associated paradigm shift from FT to CT in the management of stuttering in children and adults.